Explaining Religious Revival in the Context of Long-Term Secularization - Stolz, Jörg (Religions, 2023)
Secularization theory has often been criticized for not being able to explain counterexamples. However, secularization theorists argue that transitory religious resurgences are expected to occur even in modernizing conditions. The aim of this article is to identify mechanisms that can explain the temporary upswing of religion against the backdrop of long-term modernization. We classify the mechanisms under five broad headings: crisis, reaction, transition, state intervention, and composition. Historical examples are provided to illustrate these mechanisms. The mechanisms are not mutually exclusive and can be understood within the framework of rational action.